P086 Patient perceptions of musculoskeletal ultrasound as an educational tool in a rheumatology podiatry clinic. (23rd April 2022) - Newcombe, Lisa; Tougher, John; Kelleher, Nancy; Woodburn, Jim; Barn, Ruth
Abstract: Background/Aims: Emerging evidence suggests musculoskeletal ultrasound (MSUS) may benefit patient understanding of their inflammatory arthritis and medication adherence. The overall objective was to explore patient perceptions of MSUS when used as a patient education tool in relation to foot problems in people with rheumatic and musculoskeletal diseases (RMD). Methods: Consecutive patients attending a rheumatology podiatry clinic at the Queen Elizabeth University Hospital Podiatry Department, Glasgow, were invited to participate. To gather information on how useful MSUS was for patient understanding of their foot problems, participants completed a brief questionnaire before and after their MSUS scan. MSUS assessment of affected foot structures was conducted by a single podiatrist with MSUS training (LN) using an Esaote MyLabAlpha portable US machine. Participants were shown both grayscale and power Doppler MSUS still images with/without video clips and caliper measurements depending on the presenting complaint. Anatomical foot models were used to orientate patients to foot anatomy and corresponding MSUS images. Results: A total of 43 (12 male: 31 female) participants were recruited with a mean (SD) age of 50 (12) years and median disease duration (IQR) of 6 (1, 10) years. The most common RMD was spondylarthopathy (30%) followed by RA (23%). In this group, the rearfoot region (35%) was most frequently involved. The most frequently affected structure was tendons (30%) with multiple structures affected in 19%. A range of mechanical and inflammatory MSUS diagnoses were made. 56% of participants had not previously seen MSUS of the joints or tendons, with the remaining 44% unsure. 93% reported the MSUS scan improved understanding of their foot pain and 98% reported it will make them more likely to adhere to podiatry treatments and advice [Table 1 ]. 98% also reported that MSUS was more useful than other educational resources for understanding their foot pain. Still images were selected most frequently as the method that made the most sense to participants. Conclusion: This study provides preliminary evidence of the potential value of MSUS as an educational tool in podiatry, with potential to enhance adherence with podiatry interventions and rehabilitation programmes. Further work using a follow up design is required. Disclosure: L. Newcombe: None. J. Tougher: None. N. Kelleher: None. J. Woodburn: None. R. Barn: None.